The effects of gibberellic acid (GA3) on the harvesting time of spray type Chrysanthemum cut flowers in medium land - Herni Shintiavira; ENDANG SULISTYANINGSIH; AZIZ PURWANTORO; RANI AGUSTINA WULANDARI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Shintiavira H, Sulistyaningsih E, Purwantoro A, Wulandari RA. 2020. The effects of gibberellic acid (GA3) on the harvesting time of spray type Chrysanthemum cut flowers in medium land. Biodiversitas 21: 1723-1729. The high temperature of the medium land causes a delay in harvesting time and also decreases the diameter of Chrysanthemum cut flowers (Chrysanthemum morifolium R.). It is, however, possible to accelerate and increase the flower diameter through the use of the Gibberellic acid (GA3). This research, therefore, aimed to obtain the best GA3 concentration to accelerate harvesting time using three varieties of spray type Chrysanthemum cultivated on a medium land. The experimental design involved the use of a split-plot with three replications. The main plot varied the GA3 concentration between 0, 200, 400, and 600 mgL-1 while the subplot used the spray type Chrysanthemum varieties such us ‘Yastayuki’, ‘Arosuka Pelangi’, and ‘Socakawani’. It was applied on the 56, 63, and 70 days after planting (DAP). The data were analyzed using Analysis of Variance (ANOVA) and a further test was conducted using Duncan Multiple Range Test (DMRT) at ?=0.05. The results showed GA3 at 400 mgL-1 was the best concentration to increase the harvesting time in all varieties. However, the harvesting time of spray type without secondary branching (‘Arosuka Pelangi’) was faster than spray type with secondary branching (‘Yastayuki’ and ‘Socakawani’). The harvesting time was earlier 13, 9, and 7 days for ‘Arosuka Pelangi’,’Yastayuki’ and ‘Socakawani’ compare with control, respectively. The average diameter of the blooming flowers was also wider with 54.9 mm compared to the control treatment which was 38.7 mm.